The Great Pretender: Rectal Syphilis Mimic a Cancer. (15th September 2015) - Pisani Ceretti, Andrea; Virdis, Matteo; Maroni, Nirvana; Arena, Monica; Masci, Enzo; Magenta, Alberto; Opocher, Enrico
Abstract : Rectal syphilis is a rare expression of the widely recognised sexual transmitted disease, also known as the great imitator for its peculiarity of being confused with mild anorectal diseases because of its vague symptoms or believed rectal malignancy, with the concrete risk of overtreatment. We present the case of a male patient with primary rectal syphilis, firstly diagnosed as rectal cancer; the medical, radiological, and endoscopic features are discussed below.